Título Padrão - Mesquita, Denizete Lima de; Ferreira Gomes, Henriette (Informação em Pauta, 2023)
School library is a research theme present in several areas of knowledge, among them Information Science. This study aimed to identify the scientific productions published in the annals of the National Meeting of Research and Post-Graduation in Information Science (ENANCIB), between 2011 and 2021 that deal with the subject and the approach given by the researchers of the Working Group (GT )3 – Mediation, Circulation and Appropriation of Information from the National Association for Research and Graduate Studies in Information Science (ANCIB). As for the methodology, this study is characterized as bibliographical research, with a quantitative and qualitative approach, of a descriptive level, carried out in three stages. As a result, it was found that: between 2011 and 2021, 346 works were presented within the scope of GT-3 and of these, only 12 deal with school libraries; these were produced by 21 authorships (authors and co-authors) belonging to 5 Brazilian Universities. Thus, it is concluded that: there were few publications on school libraries, given the importance of the topic and researchers are concentrated in a small number of Universities in the South and Southeast regions of the country. However, even in a small amount, the relevance of these publications was verified to expand the discussions and dialogues in favor of the construction of school libraries capable of effectively collaborating in educational environments.